Anomalously Large Antiphase Signals from Hyperpolarized Orthohydrogen Using a MOF‐Based SABRE Catalyst. Issue 8 (11th January 2023) - Alam, Md Shahabuddin; Li, Xinlin; Brittin, Drew O.; Islam, Saiful; Deria, Pravas; Chekmenev, Eduard Y.; Goodson, Boyd M.
Abstract: Hyperpolarized orthohydrogen ( o ‐H2 ) is a frequent product of parahydrogen‐based hyperpolarization approaches like signal amplification by reversible exchange (SABRE), where the hyperpolarized o ‐H2 signal is usually absorptive. We describe a novel manifestation of this effect wherein large antiphase o ‐H2 signals are observed, with 1 H enhancements up to ≈500‐fold (effective polarization P H ≈1.6 %). This anomalous effect is attained only when using an intact heterogeneous catalyst constructed using a metal–organic framework (MOF) and is qualitatively independent of substrate nature. This seemingly paradoxical observation is analogous to the "partial negative line" (PNL) effect recently explained in the context of Parahydrogen Induced Polarization (PHIP) by Ivanov and co‐workers. The two‐spin order of the o ‐H2 resonance is manifested by a two‐fold higher Rabi frequency, and the lifetime of the antiphase HP o ‐H2 resonance is extended by several‐fold. Abstract : Addition of parahydrogen to particles comprised of an iridium‐based catalyst supported on a metal–organic framework produces dissolved orthohydrogen, but with a twist: a strongly hyperpolarized state is achieved that is enriched in the T0 sublevel, giving rise to a surprising anti‐phase signal with enhancement up to ≈500‐fold and significantly increased hyperpolarization lifetime.